From Jesus to Paul : Studies in Honour of Francis Wright Beare - Richardson, Peter (Book collections on Project MUSE., 2006)
The essays presented here intend to open afresh the complexity of the question of Paul's dependence upon and continuity with Jesus. So much attention has been given in the past to this very difficult problem that new solutions are hard to find and suspect when offered. This collection, however, demonstrates diversity in approach, stance, and conclusion. The essays often take issue with the results of current research-including that of Francis Wright Beare, in whose honour they have been produced. They consider a broad range of the recent literature and show that no satisfactory solution has y.